al-Fitri al-Tsaqafi; Nahwa al-Jadid fi al-Manhaj al-Kalami 'inda Muhammad al-Ghazali - Muhammad Shohibul Mujtaba (Universitas Darussalam Gontor, 2019)
This research was written to see one of the new methods in the development of the science of kalam, by using the book Aqidah al-Muslim by Syaikh Muhammad al-Ghazzali as the object of research. The new method is al-Fithry al-Tsaqafi. From his book, it can be analyzed that Syaikh Muhammad al-Ghazali applied the method of al-Fithry al-Tsaqafi in the development of contemporary kalam science issues. This is illustrated from the five chapters in the book. Namely: Criticism of the science of kalam, proof of the form of God, creation of nature, description of the verse